Impact of Attitudinal Dimensions of Professionalism on Employee Satisfaction and Organizational Commitment at Five Star Hotels in Baku - Guliyev, Gabil (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
In contemporary studies, the acceptance of the professionalism concept is gaining an embrace within the tourism and hospitality industry. Tourism industry is made up of various subsectors and the concept of professionalism is a relevant discourse as far as the service industry is concerned. In hospitality, there are roles which need the total commitment of employees, therefore, professionalism is suitable for employees to sustain self-discipline, and still accomplish great success on their duties. It is in the light of this necessity that this study was conducted to know the impact attitudinal dimensions of professionalism have on employee s job satisfaction and organizational commitment at five star hotels in Baku, Azerbaijan. As a result, five hundred and three (503) employees of twenty-four five star hotels responded to this survey. Based on the findings, professionalism is a viable concept among employees with a highly significant level. The implication is that professionalism is of high value towards their successes and makes it a necessity to acquire knowledge and skills to bring about efficiency. There is also a clear-cut understanding of the need to perform selfevaluations to ease the achievement of self-set goals. The researcher also found that professionalism has significant influence on the job satisfaction of employees. The employees expressed satisfaction with their work and held strong views that their job sufficiently suits their ability. This is a clear indication that professionalism supports their level of satisfaction on their present job. The study found that professionalism has significant influence on organizational commitment. This influence is justified by the willingness of employees to continue working with their present employers and pleasurable with the working conditions. This study outlined hypothesis, all of which supported the data findings and were as a result accepted. Keywords: attitude, professionalism, job satisfaction, organizational commitment.

ŐZ: Son zamanlar turizm ve konaklama sektöründe profesyonellik hızla yaygın bir kavram haline gelmektedir. Turizm endüstri çeşitli alt sektörlerden oluşuyor ve hizmet sektörü söz konusu olduğunda profesyonellik kavramı öne çıkıyor. Otelcilik sektörü önemli roller üstleniyor ve bunun içinde çalışanlardan verilen görevi istendiği gibi yapması bekleniyor. Çalışanlar profesyonellik sayesinde kendine-hakimiyet ve verilen görevi üst düzüyde uygulaya bilir. Bu çalışmanın ana maksatı Bakü, Azerbaycan beş yıldızlı otellerde profesyonelliğin çalışanların iş memnuniyyetini ve organizasyonel bağlılığını nasıl etkilediğinin boyutlarını aydınlatmaktır. Yirmi dört beş yıldızlı otelden toplanan anket sayısı 503. Elde edilen bulgular, profesyonelliğin çalışanlar arasında önemli konsept olduğunu yüksek derecede göstermektetir. Profesyonellik çalışanların başarılı olması ve bu başarının elde edilmesi için gerekli olan bilgi ve becerilerin kazanılmasını etkili bir şekilde anlatan bir kavramdır. Hedeflenen başarıya kolayca ulaşa bilmek için öz-değerlendirme yapmak net bir yaklaşımdır. Araştırma ayrıca çalışanların iş memnuniyeti üzerinde profesyonelliğin önemli etkiye sahip olduğunu açığa çıkarmıştır. Yaptıkları işin kendi yeteneklerine olan uyumu çalışanların işlerinden duyduğu memnuniyet derecesini de beraberinde getiriyor .Bu pofesyonelliğin iş memnuniyet düzeyini desteklediğinin göstergesidir. Ayrıca bu çalışma profesyonelliğin organizasional bağlılığı önemli şekilde etkilediğini ortaya koymuştur. Bu etki çalışanların mevcut işverenle çalışmaya devam etme isteğini ve iş koşularından memnuniyet derecesini aydınlatıyor. Bu çalışmada kullanılan hipotezlerin her biri veri bulgularıyla desteklenmektedir. Anahtar kelimeler: tutumsallık, porfesyonellik, iş tatmini, organizasional bağlılık.
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2016. Co-Supervisor: Assoc. Prof. Dr. Ali Öztüren, Supervisor: Prof. Dr. Turgay Avcı.
Keywords: Tourism; Employee motivation; Work-Psychological aspects-Hotel Industry--Baku; Organizational behavior; Attitude; professionalism; job satisfaction; organizational commitment